ANALISIS PENERAPAN ANGGARAN BERBASIS KINERJA (ABK) TERHADAP EFISIENSI, EFEKTIFITAS DAN AKUNTABILITAS PADA PUSAT PENDIDIKAN DAN PELATIHAN KEMENTERIAN DALAM NEGERI REGIONAL BANDUNG - Septiana Dwiputrianti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2012)
This study aims to find out the effect of the application of performance-based budgeting to performance budgetingÂ manager at the Centre for Education and Training Ministry of Home Affairs, Bandung Regional. The variables in thisstudy are the application of performance-based budgeting as an independent variable (X) and budget management performance as the dependent variable (Y). The dimensions of the indicators of variable X include the preparation phase(X1), the ratification stage (X2), the implementation phase (X3), reporting and evaluation phase (X4). While the indicators of variable Y include the dimensions of the level of efficiency (Y1), the level of effectiveness (Y2), and levels ofaccountability (Y3). The research method used is explanative research method because it intends to investigate the effect of one variable to another variable. The sampling technique used is saturated by the number of sampling techniques sample of 38 respondents. Data collection techniques are the study of literature and field research consisting of distributing questionnaires and interviews. The results shows that the application of performance-based budgeting and performance management budget is included in the Good category. Stages of preparation, ratification, implementation, reporting and evaluation of a positive effect on the level of efficiency, effectiveness, and level of accountability. It can be concluded that the application of variable performance-based budgeting has a positive effect on the performance variable budget manager at the Center for Education and Training Ministry of Interior Regional Bandung. The authors provide recommendations for improving the performance of the budget manager, by doing socialization regulations and guidelines on budget preparation and m Increasing the effectiveness of supervision and control of budget execution is managed by the managing budgets and doing so type of expenditure should consider the composition of several types of shopping and p Need to involvement of both the head and the head of the field to describe the activities and types of budgets that have been proposed by each section.